Evaluation of advanced breeding lines of sesame (Sesamum indicum L.) for seed yield and oil content: Evaluation of advanced breeding lines of sesame (Sesamum indicum L.) for seed yield and oil content - A B M SIRISHA; S K HASEENA BANU; S V S GANGADHARA RAO (Journal of Oilseeds Research, 2020)
The present investigation was carried out to evaluate the advanced breeding lines in sesame for seed yield and oil content. The experiment was conducted during kharif 2018, with eight entries (seven advanced breeding lines and one check Sarada) in randomized block design, with plot size of 3.0 x 4.5 m and spacing of 30 x15 cm. Data was recorded on the parameters viz., days to maturity, seed yield (kg/ha), oil percent and oil yield kg/ha. Among all the entries tested, YLM-146 and YLM-142 recorded significant and highest seed yield 1017 kg/ha and 963 kg/ha, respectively compared to the check Sarada (YLM-66).